Specificities of the treatment for polycystic ovary syndrome and metabolic syndrome - I.Yu. Ilina (LCC «Medicine-Inform», 2020)
I.Yu. Il'ina N.I. Pirogov Russian National Research Medical University, Moscow, Russian Federation This paper discusses polycystic ovary syndrome (PCOS), a common endocrine disorder characterized by hirsutism, anovulation, and polycystic ovaries. Insulin resistance which is considered the major causative factor for both PCOS and metabolic syndrome is emphasized. The early diagnosis of metabolic disorders which increase the risk of cardiovascular complications and the complications of pregnancy (including gestational diabetes and hypertension which may result in preeclampsia and placental abruption) is of particular importance. The presence of metabolic syndrome in PCOS is associated with poor prognosis in terms of fertility and has a negative impact on the outcomes of in vitro fertilization in infertile women with PCOS. When describing treatment approaches, the role of metformin, inositol, folates, vitamin D, and statins in treating metabolic disorders in PCOS and metabolic syndrome, reducing the risks of cardiovascular complications, and realizing fertile function is highlighted. The course of PCOS is complicated by psychic disorders (i.e., depression, anxiety, bipolar disorder, or eating disorders) which are common in these women and should be considered when prescribing medications. Keywords: polycystic ovary syndrome, insulin resistance, infertility, metabolic syndrome, cardiovascular complications, inositol, folates. For citation: Il'ina I.Yu. Specificities of the treatment for polycystic ovary syndrome and metabolic syndrome. Russian Journal of Woman and Child Health. 2020;3(4):-259. DOI: 10.32364/2618-8430-2020-3-4-254-259.